Analysis of Lean Manufacturing Implementation on E-Supply Chain Management Performance in Manufacturing Companies - Subawa Subawa; Febrisi Dwita; Muhamad Abdul Hafidzh (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study aims to determine the effect of the implementation of the lean manufacturing system on the performance of E-supply chain management. The sample for this study is a company that uses a lean manufacturing system in Cikarang, Bekasi. This research method involves using direct observation in companies regarding the use of lean manufacturing systems from the processes of receiving customer orders, calculating raw material requirements, ordering raw material requirements, production processes, and delivery processes, so that concrete data can be obtained. With this research, it will be determined whether the use of a lean manufacturing system will affect production lead time, reduce the amount of inventory, reduce inventory area, and improve delivery performance. So that from the implementation of lean manufacturing, is there any influence on the performance of E-Supply Chain Management. With E-Supply Chain Management, control and monitoring of Supply Chain Management performance can be done in real time, wherever we are as long as there is an internet network, we can control.